Efektivitas Metode Shadow Fight Terhadap Peningkatan Refleks Tanding Atlet Pencak Silat Pujo Janoko Klub - UNTAG CIREBON, FKIP; Sri Sundari; Handayani Nila Praja; Moch Iman Setiawahyu; Mia Rosalina; Vitto Fuji Pebriansyah (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
This study aims to determine the effect of shadow fighting training methods on improving throwing techniques, as well as to identify differences in throwing technique abilities before and after shadow fighting training. This study used a quantitative experimental method with a single-group pre-test and post-test design. The sample consisted of 15 athletes aged 15-25 years from a total population of 55 athletes. Shadow fighting training was given for 16 sessions over two months, six times per week. Data were collected through 10 bantingan technique tests in the pre-test and post-test. Data analysis was performed using the Shapiro-Wilk test and Paired Sample T-Test using the SPSS application. The results show a significant improvement in striking techniques with an average difference between pre-test and post-test scores of 42.4 points and a significance value of p=0.000 (p<0.05). Shadow fighting exercises are effective in strengthening muscle memory, improving coordination, and improving combat readiness without the risk of injury. Shadow fighting exercises have been proven effective in improving throwing techniques among athletes at the Pujo Janoko Pencak Silat Club. Further research is recommended with a larger sample size and a variety of measurement methods.